Validasi Multitrait-Multimethod Manifest Need Questionnaire (MNQ) Untuk Mengukur Motivasi Berprestasi Dalam Konteks Kerja - Femmy Lekahena; Alimatus Sahrah, Anwar (Jurnal Psikologi, 2022)
Validation process psycometrically on a measuring instrument which adapted to difference culture from the original version is an absolute necessity in order its application can be more accurate. The aim of this research is validating psycometrically on Manifest Need Questionnaire (MNQ) as a instrument to measure employee’s achievement motivation in work setting that adapted from American language and culture to Indonesian language and culture. The method used in this research is Multitrait-Multimethod. Validation consisted by constract validity (convergent-discriminant) and internal consistency reliability (alpha-cronbach). Multitrait-multimethod matrix was used on the analysis to identify convergent-discriminant validity (including three comparative scale: Multidimensional Work Motivation Scale, Transgression-Related Interpersonal Motivation, dan Forgiveness Scale). The results show that MNQ has validity that can accepted psychometrically (N=211) with the reliability α=0,897